HUBUNGAN JENIS PENGOBATAN ANTI TUBERKULOSIS TERHADAP KEPATUHAN MINUM OBAT ANTI TUBERKULOSIS - zuliawati, zuliawati; Girsang, Rostiodertina (Jurnal Penelitian Keperawatan Medik, 2024)
Pulmonary TB germs can infect various parts of the body and prefer parts of the body with high oxygen levels. The lungs are the main predilection site for pulmonary tuberculosis (TB) germs. Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis. Pulmonary Tuberculosis (Pulmonary TB) is an infectious disease caused by Mycobacterium Tuberculosis. The number of TB cases every year always increases with new cases and the success rate of treatment is still insufficient. Based on data from the World Health Organization (2018), there are 6.4 million people in the world infected with TB germs. In Indonesia, the number of TB cases is estimated to be 842,000 new TB cases per year (319 per 100,000 population) with 107,000 deaths per year (40 per 100,000 population). One factor that can be related to non-compliance with TB drug consumption is the type of TB treatment. The aim of the study was to identify the relationship between the type of anti-tuberculosis treatment and adherence to taking anti-tuberculosis medication. This research is a quantitative research study with a cross sectional approach. This research was carried out at the Deli Tua Community Health Center. The population of this study were pulmonary TB patients who were registered and receiving treatment at the Deli Tua Community Health Center, with a total of 68 respondents. The research results showed that there was no relationship between the type of treatment and compliance with taking anti-tuberculosis medication with a p value of 0.921. TB sufferers need to increase awareness of compliance with taking anti-tuberculosis medication.